Possibilities of operational use of reliability theory methods/Patikimumo teorijos metodų praktinio taikymo galimybės - Parasonis, Josifas (Journal of Civil Engineering and Management, 2001)
The possibilities of using methods of a reliability theory are considered from the point of view of solving three problem groups. At first, collecting representative statistical data about loadings, design schemes, physical-mechanical characteristics of materials, geometrical parameters of structures, etc. Secondly, it is necessary to investigate reliability of the applied deterministic calculation and to evaluate statistically possible inaccuracies in calculations. At last, rated probabilities of the failure of structures. Use of reliability theory methods can be extended. It is necessary to accumulate statistical data about changes in time of strength and deformation properties of structural materials for reinforced concrete structures, variability of concrete strength in structures. It is necessary to accumulate statistics about actions and to solve the problem of values of factors. It has been marked that the studies of reliability of the design methods are realized for rather simple members subjected to bending and compression without consideration of materials properties in time. The expediency of experimental research on reliability of structures is discussed. Taking into account our experience of influence on reliability of frames of one-storey industrial buildings of the precision of geometrical parameters of mounting, it is expedient study reliability separately from design, mounting and maintenance stages. The new approach to a reliability estimation on the basis of ensuring functional reliablity of buildings is discussed. Thus the probability of failure should be equal to the magnitude of probability.Article in Lithuanian.First Published Online: 30 Jul 2012